Putative effects of QTL on the development of cardiomyopathy syndrome (CMS) in natural infected Atlantic salmon (Salmo salar) in marine production - Seljelid, Siri Magnusson (The University of Bergen, 2024)
Masteroppgave i fiskehelse FISK399 MAMN-FISK